Management News and Notes (Academy of Management Journal, 1967)
The article presents officer election results at different division meetings of the Academy of Management. The article announces the election results for the Eastern Division meetings held April 14–15, 1967; the results include Walter Hill as President, C. Wickham Skinner as President-elect, and Robert Schellenberger as Vice President. The article also announces election results for the Western Division meeting on March 16–18, 1967 and the Midwest Division on April 7–8, 1967.